Enhanced anti-cancer effects of oestrogen and progesterone co-therapy against colorectal cancer in males - Mahbub, Amani A.; Aslam, Akhmed; Elzubier, Mohamed E.; El-Boshy, Mohamed; Abdelghany, Abdelghany H.; Ahmad, Jawwad; Idris, Shakir; Almaimani, Riyad; Alsaegh, Aiman; El-Readi, Mahmoud Zaki; Baghdadi, Mohammed A.; Refaat, Bassem (Frontiers in Endocrinology, 2022)
Although ovarian sex steroids could have protective roles against colorectal cancer (CRC) in women, little is currently known about their potential anti-tumorigenic effects in men. Hence, this study measured the therapeutic effects of 17β-oestradiol (E2) and/or progesterone (P4) against azoxymethane-induced CRC in male mice that were divided into (n = 10 mice/group): negative (NC) and positive (PC) controls, E2 (580 µg/Kg/day; five times/week) and P4 (2.9 mg/Kg/day; five times/week) monotherapies, and concurrent (EP) and sequential (E/P) co-therapy groups. Both hormones were injected intraperitoneally to the designated groups for four consecutive weeks. Similar treatment protocols with E2 (10 nM) and/or P4 (20 nM) were also used in the SW480 and SW620 human male CRC cell lines. The PC group showed abundant colonic tumours alongside increased colonic tissue testosterone levels and androgen (AR) and oestrogen (ERα) receptors, whereas E2 and P4 levels with ERβ and progesterone receptor (PGR) decreased significantly compared with the NC group. E2 and P4 monotherapies equally increased ERβ/PGR with p21/Cytochrome-C/Caspase-3, reduced testosterone levels, inhibited ERα/AR and CCND1/survivin and promoted apoptosis relative to the PC group. Both co-therapy protocols also revealed better anti-cancer effects with enhanced modulation of colonic sex steroid hormones and their receptors, with E/P the most prominent protocol. In vitro, E/P regimen showed the highest increases in the numbers of SW480 (2.1-fold) and SW620 (3.5-fold) cells in Sub-G1 phase of cell cycle. The E/P co-therapy also disclosed the lowest percentages of viable SW480 cells (2.8-fold), whilst both co-therapy protocols equally showed the greatest SW620 apoptotic cell numbers (5.2-fold) relative to untreated cells. Moreover, both co-therapy regimens revealed maximal inhibitions of cell cycle inducers, cell survival markers, and AR/ERα alongside the highest expression of cell cycle suppressors, pro-apoptotic molecules, and ERβ/PGR in both cell lines. In conclusion, CRC was associated with abnormal levels of colonic sex steroid hormones alongside aberrant protein expression of their receptors. While the anti-cancer effects of E2 and P4 monotherapies were equal, their combination protocols showed boosted tumoricidal actions against CRC in males, possibly by promoting ERβ and PGR-mediated androgen deprivation together with inhibition of ERα-regulated oncogenic pathways.